Evidence from clinical trials for the use of valproic acid in solid tumors: focus on prostate cancer. (May 2013) - Goyal, Jatinder; Rodriguez, Ronald
The progression of prostate cancer to an androgen-unresponsive state is challenged with unmet therapeutic needs. Valproic acid is a HDAC inhibitor that has recently been found to possess antitumor activity in diverse tumor types. Its role in prostate cancer has been explored in multiple clinical trials on solid tumors. Results from these trials have shown that it offers an encouraging avenue of treatment. Valproic acid was well tolerated in most of these trials without causing any significant life-threatening toxicities. The combination of valproic acid with other chemotherapy agents has been shown to be safe, tolerable and efficacious in prostate cancer. Multiple trials are underway combining various antineoplastic agents with valproic acid in an attempt to achieve a broad therapeutic index. Although the underlying mechanisms behind the efficacy of valproic acid remain to be elucidated, it entails a promising strategy for development of an effective anticancer therapy.